Characterization of surface roughness of unworn hydrogel contact lenses at a nanometric scale using methods of modern metrology - TALU, Stefan (Polymer engineering and science, 2013)
The aim of this study was to qualitatively and quantitatively characterize the optic surface topography of unworn hydrogel contact lenses (CLs) using atomic force microscopy (AFM) analysis and methods of modern metrology. The CLs used in this study were vifilcon A (Focus® Monthly Toric Visitint® model, CIBA Vision Corp.). AFM analysis was performed in Tapping Mode™ in an aqueous environment. The surface roughness analysis was based on six quantitative statistical parameters: arithmetic mean deviation of the surface (Sa), root mean square deviation of the surface (Sq), skewness of the topography height distribution (Ssk), kurtosis of the topography height distribution (Sku), 10‐point average of the absolute heights (Sz), and vertical distance between highest peak and lowest surface point (St). These parameters were determined across different square areas (1, 4, 9, 16, and 25 μm2). The surface roughness parameter values were found to be dependent on the examined surface area. The values of Sa, Sq,|Ssk|, Sz, and St parameters increase with the increasing size of the scanning area, an opposite effect of that observed for the Sku parameter values. The proposed methodology might potentially have implications for the future testing of contact lens hydrophilic polymers. POLYM. ENG. SCI., 53:2141–2150, 2013. © 2013 Society of Plastics Engineers